2002
DOI: 10.1309/7y7n-m1wm-r0yk-m2va
|View full text |Cite
|
Sign up to set email alerts
|

MUC4 Expression Increases Progressively in Pancreatic Intraepithelial Neoplasia

Abstract: Pancreatic adenocarcinoma is believed to develop from histologically identifiable intraductal lesions known as pancreatic intraepithelial neoplasias (PanINs) that undergo a series of architectural, cytologic, and genetic changes, a progression model similar to the adenoma-carcinoma sequence in the colon. The apomucin MUC4 has been implicated in invasive pancreatic adenocarcinoma. MUC4 expression is not detectable at the RNA level in normal pancreas but is detectable at high levels in invasive pancreatic adenoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
211
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(237 citation statements)
references
References 24 publications
22
211
2
2
Order By: Relevance
“…MUC5B is moderately expressed, while MUC1 and MUC5AC are weakly detected in the adult pancreas (Yonezawa et al, 1997;Yonezawa et al, 1999;Andrianifahanana et al, 2001;Terris et al, 2002). We have previously reported that the overexpression of the MUC1 gene as well as the aberrant expression of MUC4 were associated with the development and progression of PC (Swartz et al, 2002;Park et al, 2003). In the normal pancreas, the expression of MUC1 is confined to the apical membrane of the intralobular ductules.…”
Section: Abnormal Expression Of Mucin Genes In Pcmentioning
confidence: 91%
See 1 more Smart Citation
“…MUC5B is moderately expressed, while MUC1 and MUC5AC are weakly detected in the adult pancreas (Yonezawa et al, 1997;Yonezawa et al, 1999;Andrianifahanana et al, 2001;Terris et al, 2002). We have previously reported that the overexpression of the MUC1 gene as well as the aberrant expression of MUC4 were associated with the development and progression of PC (Swartz et al, 2002;Park et al, 2003). In the normal pancreas, the expression of MUC1 is confined to the apical membrane of the intralobular ductules.…”
Section: Abnormal Expression Of Mucin Genes In Pcmentioning
confidence: 91%
“…Atypical intraductal lesions can progress to invasive adenocarcinoma (Brat et al, 1998). MUC4 is expressed by metasplastic ducts and its expression increases with a higher grade of PanINs (Swartz et al, 2002;Park et al, 2003). Similarly, MUC1 expression also increases with the progression of PanIN lesions ( Figure 1B), whereas MUC2 expression remains unchanged (Adsay et al, 2002).…”
Section: Abnormal Expression Of Mucin Genes In Pcmentioning
confidence: 97%
“…gains on 3q29, we evaluated gene expression data in HNSCC published by Ginos et al (2004) for genes on 3q29 and found frequent overexpression of several genes, including mucin 4 (MUC4), a gene found to be amplified overexpressed in pancreatic cancers (Swartz et al, 2002) with oncogenic abilities (Singh et al, 2004). MUC4 mRNA levels were upregulated in at least 35% HNSCC cases.…”
Section: Subclassification Of Amplicons On Chromosome 3q263-q29mentioning
confidence: 99%
“…Recent studies have provided compelling evidence implicating the MUC4 mucin in the pathogenesis of pancreatic cancer (Komatsu et al, 2000;Swartz et al, 2002;Singh et al, 2004). Expression analysis of MUC4 in increasing grade pancreatic intraepithelial neoplastic lesions (PanINs) and pancreatic adenocarcinoma demonstrated a positive correlation of MUC4 with the disease progression (Swartz et al, 2002). Moreover, silencing of MUC4 expression in pancreatic cancer cells led to reduced tumor growth and metastasis, suggesting an important role of MUC4 in pancreatic tumour development (Singh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%